The Inequality-Growth Relationship - An Empirical Reassessment - Galina Kolev; Judith Niehues (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Recently, some influential empirical studies found evidence in favor of a negative relationship between income inequality and economic growth, implying the conclusion that inequality reducing policies will foster economic growth. The studies have in common that they all rely on the System GMM dynamic panel estimator. We argue that this estimator is most likely to suffer from a severe weak instrument problem in the inequality-growth setting because lagged differences of inequality have practically no explanatory power for currrent inequality levels. Thus, it is biased in the direction of OLS and fails to control for country heterogeneity. Using traditional Fixed Effects models or Difference GMM estimators yields positive coefficents on the inequality variable. Furthermore, we find evidence for a non-linear relationship between inequality and growth when considering a sample of developed and developing economies. Thus, the effect of net income inequality on growth seems to be negative only for less-developed countries and for countries with high levels of inequality.
Keywords: O15; O47; H23; 330